JOINT REGIONAL MILITARY ACT TO CURB CORONA VIRUS PANDEMIC - Thomas Atmaja Adi; Ganesha Wandawa; Wahyu Hidayat (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2021)
Threats to the security of the Republic of Indonesia are classified as military and non-military threats. One of the non-military threats is the danger of an epidemic, which includes a threat with a public safety dimension. The growth of novel coronavirus (2019-nCoV) cases has been very fast. As of August 4, 2020, globally 18.14 million cases were confirmed worldwide with 691,013 deaths or a Case Fatality Ratio (CFR) of 3.8%. The 2019-nCoV Outbreak became a COVID-19 pandemic which has an impact on public health and the world economy. ASEAN Plus member countries are deploying militaries to help contain the spread and control the effects of this pandemic. The military is deployed because it is considered a trained resource and is better prepared to deal with emergencies. The purpose of this study is to analyse the joint action of the regional military in the face of the COVID-19 pandemic. This study uses an explanative qualitative method using NVivo as a data processing tool and data analysis using Soft System Methodology (SSM). The results of this study found that the joint regional military actions that have been carried out to stem the spread of COVID-19 are dominated by activities carried out by the ASEAN Center of Military Medicine (ACMM) as the leading sector, activities that have been carried out are the exchange of information and sharing practical activities in managing COVID-19, holding a Tabletop Exercise (TTX) for public health emergency response, joint research and sharing health materials among ASEAN Plus member countries. Meanwhile, the ASEAN Plus network of biological and radiological defense experts has yet to show specific activities to curb the COVID-19 pandemic.